SOCIAL PROBLEMS AND ENVIRONMENT: ROLE OF SUPREME COURT: सामाजिक समस्याएं व पर्यावरण: उच्चतम न्यायालय की भूमिका - Dixit, Mukesh (International Journal of Research -GRANTHAALAYAH, 2015)
Humans have a deep connection to the environment. Ever since man came to this earth, he has kept the environment with him. The sun, moon, earth, mountains, forests, rivers, oceans, water etc. have been used by humans since the beginning of human development. Human beings have used natural wealth from the beginning to obtain wood, food, clothes, medicines etc. in their daily life and continue to the present. With social change, environment has been affected in industrial development and population growth. Due to industrialization, a person has become an active factor to change the environment according to his needs. Destruction of forests, air and aquatic pollution and increasing use of pesticides for agricultural production have led to extensive changes in the environment. Various types of diseases like famine, drought, earthquake, earthquake and epidemic are causing the destruction of human civilization. Today the environment is being polluted with the extreme development of industrialization. पर्यावरण से मानव का गहरा संबंध है। मनुष्य जब से इस पृथ्वी पर आया, उसने पर्यावरण को अपने साथ जोड़े रखा है। सूर्य, चन्द्रमा, पृथ्वी, पर्वत, वन, नदियां, महासागर, जल इत्यादि का प्रयोग मनुष्य मानव विकास के आरंभ से करता आ रहा है। मनुष्य अपने दैनिक जीवन में लकड़ी, भोजन, वस्त्र, दवायें इत्यादि प्राप्त करने हेतु प्राकृतिक सम्पदा का शुरू से उपयोग किया है और वर्तमान मे निरंतर जारी है। सामाजिक परिवर्तन के साथ औद्योगिक विकास एवं जनसंख्या वृद्धि में पर्यावरण को प्रभावित किया है। औद्योगीकरण के कारण व्यक्ति आज अपनी आवश्यकता के अनुरूप पर्यावरण को बदलने के लिये सक्रिय कारक बन गया है। वनो का विनाश वायु एवं जलीय प्रदूषण एवं कृषि उत्पादन हेतु कीटनाशक दवाओं के बढ़ते हुए प्रयोग ने वातावरण में व्यापक परिवर्तन किये है। अकाल सूखा अतिवृष्टि भूकम्प एवं महामारी जैसे विभिन्न प्रकार के रोग मानव सभ्यता के विनाश के कारण बने हुए हैं। आज औद्योगीकरण के चरम विकास के साथ पर्यावरण प्रदूषित हो रहा है।